Aspirin and Acetaminophen Use and the Risk of Cervical Cancer. Issue 3 (July 2015) - Friel, Grace; Liu, Cici S.; Kolomeyevskaya, Nonna V.; Hampras, Shalaka S.; Kruszka, Bridget; Schmitt, Kristina; Cannioto, Rikki A.; Lele, Shashikant B.; Odunsi, Kunle O.; Moysich, Kirsten B.
<x xml:space="preserve">Abstract</x> Objective In this study, we investigated whether regular use of aspirin or acetaminophen was associated with risk of cervical cancer in women treated at an American cancer hospital. Methods This case-control study included 328 patients with cervical cancer and 1, 312 controls matched on age and decade enrolled. Controls were women suspected of having but not ultimately diagnosed with a neoplasm. Analgesic use was defined as regular (at least once per week for ≥6 months), frequent (≥7 tablets/week), very long term (≥11 years), or frequent, long term (≥7 tablets per week for ≥5 years). Results Compared to nonusers, frequent aspirin use was associated with decreased odds of cervical cancer (odds ratio, 0.53; 95% confidence interval, 0.29-0.97). A slightly larger association was observed with frequent, long-term use of aspirin (odds ratio, 0.46; 95% confidence interval, 0.22-0.95). Acetaminophen use was not associated with the risk of cervical cancer. Conclusions Our findings suggest that frequent and frequent, long-term use of aspirin is associated with decreased odds of cervical cancer. To our knowledge, this is the first US-based study examining these associations. Given the widespread use of nonsteroidal anti-inflammatory drugs and acetaminophen worldwide, further investigations of the possible role of analgesics in cervical cancer, using a larger sample size with better-defined dosing regimens, are warranted.